Automatic EMI filter design for power electronic converters oriented to high power density - Giglia, Graziella; Ala, Guido; Di Piazza, Maria; Giaconia, Giuseppe; Luna, Massimiliano; Vitale, Gianpaolo; Zanchetta, Pericle (MDPI, 2018)
In this paper, a complete computer aided procedure based on the power density concept and aimed at the automatic design of EMI filters for power electronic converters is presented. It is rule-based, and it uses suitable databases built-up by considering information on passive components available from commercial datasheets. The power density constraint is taken into consideration by imposing the minimization of the filter volume and/or weight; nevertheless, the system in which the automatically designed filter is included satisfies the electromagnetic compatibility standards limits. Experimental validations of the proposed procedure are presented for two real case studies, for which the performance and the size of the best filter design are compared with those related to a conventionally designed one.